Genotypic Variation for Salinity Tolerance in Cenchrus ciliaris L. - Al-Dakheel, Abdullah J.; Hussain, M. Iftikhar (Frontiers in Plant Science, 2016)
Scarcity of irrigation water and increasing soil salinization has threatened the sustainability of forage production in arid and semi-arid region around the globe. Introduction of salt-tolerant perennial species is a promising alternative to overcome forage deficit to meet future livestock needs in salt-affected areas. This study presents the results of a salinity tolerance screening trial which was carried out in plastic pots buried in the open field for 160 buffelgrass (Cenchrus ciliaris L.) accessions for three consecutive years (2003–2005). The plastic pots were filled with sand, organic, and peat moss mix and were irrigated with four different quality water (EC 0, 10, 15, and 20 dS m−1). The results indicate that the average annual dry weights (DW) were in the range from 122.5 to 148.9 g/pot in control; 96.4–133.8 g/pot at 10 dS m−1; 65.6–80.4 g/pot at 15 dS m−1, and 55.4–65.6 g/pot at 20 dS m−1. The highest DW (148.9 g/pot) was found with accession 49 and the lowest with accession 23. Principle component analysis shows that PC-1 contributed 81.8% of the total variability, while PC-2 depicted 11.7% of the total variation among C. ciliaris accessions for DW. Hierarchical cluster analysis revealed that a number of accessions collected from diverse regions could be grouped into a single cluster. Accessions 3, 133, 159, 30, 23, 142, 141, 95, 49, 129, 124, and 127 were stable, salt tolerant, and produced good dry biomass yield. These accessions demonstrate sufficient salinity tolerance potential for promotion in marginal lands to enhance farm productivity and reduce rural poverty.